God and a ‘Little Bit of Magic’: Faith and Healing through the Lens of Cambodian Trauma Survivors - Zoe Wyatt; K. Morgan Welton (International Journal of Social Science and Religion (IJSSR), 2022)
Trauma is a global phenomenon that affects millions each year. Recovery from trauma is challenging and approaches vary between cultures and models. Faith and spirituality have long-been traditional modes for healing in cultures worldwide. However, through a largely Western-dominated medical model of treatment, healing through religion and spirituality had been often overlooked in favor of medical diagnoses and psychiatric treatment. The ability to recover from traumatic circumstances and adversity is known as resilience. Yet there is limited research available on how faith and spirituality may build resilience in the aftermath of trauma and its application in developing countries, such as Cambodia. The aim of this qualitative study was to understand what factors, including faith and spirituality, had enabled the recovery from trauma of Cambodian young people, through the collection of their oral narratives. The young people reported that coping strategies, such as faith and spirituality, played a role in in transforming their lived traumatic experiences into strengths. This paper explores faith as a resilience factor and how faith and spirituality may support healing and positive-growth outcomes for young Cambodians recovering from trauma.